Legume-legume complementarity for sustainable pasture development in the tropics - Peters, Michael; Tarawali, Shirley A.; Schultze-Kraft, Rainer; Musa, A. (International Grassland Society, 1997)
The use of legume-legume mixtures to alleviate limitations of individual species in legume based technologies was investigated in subhumid Nigeria. The results indicate the potential of legume mixtures, through processes of complementation and compensation, to reduce the risk of legume establishment and survival and thus ensure sustainable legume yields and percentages. The implications for on-farm adoption of forage legumes are discussed.